Pengembangan Model Pembelajaran Flipped Classroom untuk Meningkatkan Hasil Belajar Sejarah Kebudayaan Islam (SKI) di Madrasah Tsanawiyah Miftahul Qulub Tawar Gondang Mojokerto - Misluhah (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2018)
Learning model based on Flipped Classroom is one of the student-centered learning model to improve the effectiveness of learning. It is therefore important that educators understand their students' academic and social background before reflecting on and planning their lessons, the pedagogical techniques they want to use and the type of assessment they believe will engage the student in the learning process. The purpose of this development are: 1) Developing the correct flipped classroom learning model used for MI Al Muhsinun Mojokerto City 2) Improving learning outcomes by using the flipped classroom learning model in Sejarah Kebudayaan Islam (SKI) learning in MI Al Muhsinun Mojokerto City. From the results of this research development can be concluded: 1) Expert validation and testing results, flipped classroom learning model is feasible to be used for the subject of Sejarah Kebudayaan Islam (SKI), because the developed product is not revised by the expert but from the results of the dissemination of student questionnaires that must be revised : (a) Improving the model's appearance or changing its learning strategy, and (b) increasing the use of resources in applying the model. 2) Making product development model through social media can improve student learning result of Sejarah Kebudayaan Islam (SKI) in MI Al Muhsinun Mojokerto City. From the experimental class, there is an increase of learning completeness from Pre Test and Post Test that is 78.78% each up to 92.63%.